Effects of Macrofungal Polysaccharides Combined with Vemurafenib on Melanoma and Its Associated Mechanism. (24th October 2019) - Wu, Wenya; Su, Zhigang; Fan, Shasha
Abstract : Fungal polysaccharides have demonstrated various biological functions such as antitumor, immune regulation, and antioxidant activities. It has also been reported to be beneficial in reshaping the immune system's surveillance on tumor cells and in helping the immune system kill tumor cells. In this study, a melanoma mouse model was constructed, and a macrofungal polysaccharide (MFPS) extracted from Pleurotus ostreatus combined with Vemurafenib monoclonal antibody was used to study their effects against melanoma and its antitumor mechanism by using the lactate dehydrogenase release assay, enzyme-linked immunosorbent assay, and flow typing assay. Results indicated that MFPS enhanced the inhibitory effect of Vemurafenib on tumor growth in melanoma-bearing mice and the secretion of cytokines IFN- γ and IL-12 in PBMCs of melanoma-bearing mice. In addition, the combination of MFPS1 and Vemurafenib can enhance the immunomodulatory activity of melanoma-bearing mice as well as elicit the activation and proliferation of B cells and T cells.